2022
DOI: 10.3390/app122211872
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Experimental Study on Polymer Flooding in High-Temperature and High-Salinity Heavy Oil Reservoir

Abstract: Polyacrylamide (HPAM) and other traditional polymers have poor temperature resistance and salinity tolerance and do not meet the needs of high-temperature and high-salinity reservoirs. In this study, a new temperature-resistant and salinity-tolerant polymer QJ75-39 was synthesized using acrylamide (AM) as a hydrophilic monomer, 1-acrylamide-2-methylpropanesulfonic acid (AMPS) and N-vinylpyrrolidone (NVP) as functional monomers and DS-16 as a hydrophobic monomer. Through laboratory experiments, the properties (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In addition, the fivemembered ring of pyrrolidone enhances the rigidity of the polymer chain [49,50]. All of these properties are beneficial for improving the thermal stability of the polymer [56,57].…”
Section: Thermogravimetric Analyses (Tga)mentioning
confidence: 99%
“…In addition, the fivemembered ring of pyrrolidone enhances the rigidity of the polymer chain [49,50]. All of these properties are beneficial for improving the thermal stability of the polymer [56,57].…”
Section: Thermogravimetric Analyses (Tga)mentioning
confidence: 99%
“…This bond leads to the deformation and coiling of polymer molecules and, accordingly, a signi cant reduction in viscosity and may even result in polymer precipitation (Chauveteau and Zaitoun, 1981). In addition to salinity and hardness, temperature is also a crucial factor affecting the performance of polymer ooding (Zhang et al, 2022). An increase in temperature accelerates the speed of polymer hydrolysis and, consequently, reduces viscosity and possible sedimentation (Rashidi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These factors make economically efficient production extremely challenging [7]. After years of water injection development practice, it has been observed that due to the high viscosity of crude oil, significant differences in oil-water mobility, and severe reservoir heterogeneity, it is prone to forming preferential water flow channels, leading to limited water flooding effectiveness [8,9]. Through the implementation of heavy oil cold production technologies such as foam flooding, chemical viscosity reduction, and gas injection cycles, the water flooding recovery rate has improved.…”
Section: Introductionmentioning
confidence: 99%